2020
DOI: 10.1177/1096348020946383
|View full text |Cite
|
Sign up to set email alerts
|

How To Build a Better Robot . . . for Quick-Service Restaurants

Abstract: Hospitality firms are exploring opportunities to incorporate innovative technologies, such as robotics, into their operations. This qualitative study used focus groups to investigate diner perspectives on issues related to using robot technology in quick-service restaurant (QSR) operations. QSR guests have major concerns regarding the societal impact of robotics entering the realm of QSR operations; the cleanliness and food safety of robot technology; and communication quality, especially voice recognition, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 41 publications
2
35
1
Order By: Relevance
“…Utilitarian value suggests that JOSM customers will have more confidence in the accuracy and consistency of the service provided, whereas service robot's hedonic value relates to fun and entertainment (Arnold and Reynolds, 2003;Lu et al, 2019;Ryan and Deci, 2001). Service providers implement anthropomorphic service robots to create value and encourage customer loyalty (Blut et al, 2021;Zemke et al, 2020). Therefore, for our context of hospitality services, we expect that being perceived as a human as the first degree of social response (anthropomorphism) translates into the provision of the core service such as serving food and drink rather than into entertaining guests.…”
Section: Hypotheses Development and Conceptual Modelmentioning
confidence: 99%
“…Utilitarian value suggests that JOSM customers will have more confidence in the accuracy and consistency of the service provided, whereas service robot's hedonic value relates to fun and entertainment (Arnold and Reynolds, 2003;Lu et al, 2019;Ryan and Deci, 2001). Service providers implement anthropomorphic service robots to create value and encourage customer loyalty (Blut et al, 2021;Zemke et al, 2020). Therefore, for our context of hospitality services, we expect that being perceived as a human as the first degree of social response (anthropomorphism) translates into the provision of the core service such as serving food and drink rather than into entertaining guests.…”
Section: Hypotheses Development and Conceptual Modelmentioning
confidence: 99%
“…Most hospitality service robot research is conducted in general service or hotel settings (Belanche et al , 2020a; Choi et al , 2020; Shin and Jeong, 2020). The few studies in the restaurant context (Belanche et al , 2020b; Cha, 2020; Zemke et al , 2020) have focused on consumers’ intention to use or perceptions before the actual service stage. Yet, consumers’ perceptions may be further shaped during the consumption stage or service encounter.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Different from general service settings, the restaurant context is unique in that robotic involvement has a more diverse presence across the multilayered service system. Some restaurants program robots to assume the service role of providing interactional services directly to customers, whereas others may involve robots in more backstage roles and processes such as food production, preparation and cooking (Zemke et al, 2020). Existing Robotic involvement in the service encounter restaurant business models have attempted to involve robots in various service functions and roles across a multilayered service system.…”
Section: Robotic Involvement In the Restaurant Industrymentioning
confidence: 99%
“…Hwang et al (2020) used a survey approach to examine the impact of motivated consumer innovativeness on customers' perceptions of robotic restaurants' image and subsequent word-of-mouth intentions as moderated by product knowledge. Zemke et al (2020) conducted a focus group to assess consumers' perceptions of issues related to using robot technology in quick-service restaurants. Zhu and Chang (2020) found that robots with (vs without) humanoid hands can lead to better food quality prediction via enhanced warmth and competence perceptions.…”
Section: Robotic Involvement In the Restaurant Industrymentioning
confidence: 99%